2012
DOI: 10.1007/s12094-012-0892-1
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative electron beam radiotherapy for newly diagnosed and recurrent malignant gliomas: feasibility and long-term outcomes

Abstract: IOERT is a feasible technique and can be viewed as a tool in the treatment of newly diagnosed or recurrent brain gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The mean age of the whole group was 51.5 years (21-81 years). With regard to radiation treatment, the mean delivered dose was 59.5 Gy (range: 40-76 Gy), and three patients received intraoperative radiation boost (IORT) with doses varying from 6 to 12.5 Gy, according to the institutional protocol at that time [8]. The mean interval between first treatment and recurrence was 23.2 months (range: 1 to 196 months), with this interval being shorter in glioblastoma patients (mean: 13.5 months, range: 1-60 months) and larger in oligodendroglioma patients (mean: 54.7 months, range: 9-196 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the whole group was 51.5 years (21-81 years). With regard to radiation treatment, the mean delivered dose was 59.5 Gy (range: 40-76 Gy), and three patients received intraoperative radiation boost (IORT) with doses varying from 6 to 12.5 Gy, according to the institutional protocol at that time [8]. The mean interval between first treatment and recurrence was 23.2 months (range: 1 to 196 months), with this interval being shorter in glioblastoma patients (mean: 13.5 months, range: 1-60 months) and larger in oligodendroglioma patients (mean: 54.7 months, range: 9-196 months).…”
Section: Methodsmentioning
confidence: 99%
“…Re-irradiation has been utilized in this setting for years and remains a feasible option, although there is always the concern of a relatively high risk of toxicity [7][8][9][10][11][12]. Modern high-precision conformal techniques, including stereotactic radiosurgery (SRS), have the power to improve the therapeutic ratio by delivering high biologically equivalent doses while reducing high-dose RT to normal brain tissues [7].…”
Section: Introductionmentioning
confidence: 99%
“…Structural limitations of the applicator tube have restricted use to cavities with clear line-of-sight parameters, although the recently described potential to link IOERT delivery devices to electromagnetic surgical navigation systems could afford access to previously unattainable targets (10,11). Despite decades of use in non-cranial sites, only a single institutional experience has been published describing intracranial use in high-grade glioma (12). Low-energy X-ray intraoperative radiotherapy (LEX-IORT) uses a 30-to 50-kV isotropic X-ray source with either fixed diameter rigid spherical applicators (Intrabeam ® , Carl Zeiss Meditec AG, Jena, Germany) or miniaturized X-ray source balloon applicators (Xoft ® , San Jose, CA, USA).…”
Section: Iort Nomenclaturementioning
confidence: 99%
“…In the largest study of IOERT in HGG, Schueller et al reported 71 total patients, 52 of which received a 20-Gy boost followed by 60-Gy EBRT for newly diagnosed tumors without significant improvement in OS or PFS intervals (31). Usychkin et al provided an additional description of use of IOERT, both in newly diagnosed and recurrent glioma patients, including anaplastic astrocytoma, GBM, and anaplastic oligodendroglioma based on contemporaneous WHO classifications (12). Of the 32 patients treated, nearly half represented recurrent disease (47%) with a subtle dose reduction of a median 10 Gy for recurrent tumors from 12.5 Gy for newly diagnosed disease.…”
Section: High-grade Gliomamentioning
confidence: 99%
See 1 more Smart Citation